Transcatheter arterial infusion for advanced hepatocellular carcinoma: Who are candidates? - Suzuki, Eiichiro (World J Gastroenterol, 2015)
AIM: To elucidate anticancer effects of transcatheter arterial infusion chemotherapy (TAI) in patients with hepatocellular carcinoma (HCC). METHODS: Data from a total of 95 patients with HCC who received TAI were analyzed retrospectively. The efficacy of TAI was evaluated according to the Response Evaluation Criteria in Cancer of the Liver. Overall survival was calculated from the date of initial treatment to the date of death or last follow-up. Survival curves were calculated by the Kaplan-Meier method, and differences in survival were evaluated by the log rank test. Clinical variables that were identified as statistically different by a univariate analysis were included into the Cox proportional hazard regression model for multivariate analysis. A prognostic index based on the regression coefficients derived from variables identified by the multivariate analysis was constructed. Stratification of the patients was conducted using this prognostic index. RESULTS: The patient group was comprised of 76 men and 19 women with an average age of 68 years (range: 37-82 years). Six patients (6.3%) showed complete response and 18 patients (18.9%) showed partial response, for an overall response rate of 25.2%. The median overall survival was 27.6 mo, and the proportions of survivors at 1, 2, and 5 years were 67.4%, 54.0%, and 17.4%, respectively. Multivariate analysis demonstrated that no prior transcatheter arterial chemoembolization, lactate dehydrogenase < 230 IU/L, and performance status of 0 were the independent favorable prognostic factors. The development of a 0-3-point prognostic score index was based on the sum of these three prognostic factors. Subsequently, the patients were categorized into three groups: those with a good (prognostic index = 0-1; n = 54), intermediate (prognostic index = 2; n = 26), or poor (prognostic index = 3; n = 15) prognosis. The median survival times in these three groups were 41.0, 21.2, and 6.8 mo, respectively (P < 0.01). CONCLUSION: Our simple prognostic index may be helpful for management of patients in determining treatment strategies for advanced HCC in the era of molecularly targeted therapy.